1999
DOI: 10.1111/j.1740-8261.1999.tb00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Encephalitis in a Yorkshire Terrier: Clinical, Imaging, and Pathologic Findings

Abstract: A 5-year-old, male Yorkshire Terrier had chronic and progressive neurologic signs compatible with lesions in the right brain stem and right forebrain. In magnetic resonance images of the brain there were multifocal lesions at different stages of evolution, consistent with an inflammatory disease. The lesions were located in the white matter of the cerebrum, in the diencephalon and mesencephalon. These lesions were hypointense in T1-weighted images and hyperintense in T2-weighted images with no mass effect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…The disease primarily affecting the cerebral hemispheres has been described in Pug, Maltese, and Yorkshire terrier [6][7][8][9][12][13][14]. Even though the cause of this disease is unknown, the brain lesions are quite similar to those of alpha herpes virus meningoencephalitis in human beings [6].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The disease primarily affecting the cerebral hemispheres has been described in Pug, Maltese, and Yorkshire terrier [6][7][8][9][12][13][14]. Even though the cause of this disease is unknown, the brain lesions are quite similar to those of alpha herpes virus meningoencephalitis in human beings [6].…”
mentioning
confidence: 99%
“…However, the microcavitations, the necrosis and the extensive sclerosis are different features from GME [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the Pug, several other breeds of dog develop NME [3,6,7]. In our previous study [4], we found that both Pugs and non-Pug dogs with NME possess anti-GFAP autoantibodies in the CSF.…”
mentioning
confidence: 73%